CT response of primary tumor and CA19-9 predict resectability of metastasized pancreatic cancer after FOLFIRINOX - Tanaka, Masayuki; Heckler, Max; Mihaljevic, André Leopold; Sun, Huihui; Klaiber, Ulla; Heger, Ulrike; Büchler, Markus W.; Hackert, Thilo (European journal of surgical oncology, 2019)
Background - Effective chemotherapy protocols are currently changing the treatment options for metastasized pancreatic cancer. Survival benefits after synchronous metastasectomy have been reported for selected patients. We set out to assess predictive factors of resectability for synchronous metastases after FOLFIRINOX. - Methods - Consecutive patients with metastatic pancreatic cancer undergoing surgery after FOLFIRINOX between 2011 and 2017 were identified from a prospectively collected database. Surgery following chemotherapy was indicated in patients with no more than six metastatic lesions, no progression detected on CT, and technically resectable disease. Patients who received synchronous metastasectomy were compared with patients who received explorative laparotomy or palliative surgery in terms of predictors of resectability and overall survival. In patients undergoing resection, prognostic factors were examined. - Results - Of 101 patients scheduled for surgery after FOLFIRINOX, synchronous metastasectomy was performed in 43 cases (43%) and non-resection surgery in 58 cases (57%). The shrinkage rate of the primary tumor on CT (P=0.04) and the postchemotherapy serum CA19-9 concentration (P=0.02) were associated with resectability. The median overall survival of the patients undergoing metastasectomy was longer than that of the patients without resection (21.9 months vs 16.4 months, P=0.006). Postchemotherapy serum CA19-9 value (P=0.04) and lymph node ratio (P=0.01) were prognostic factors in the patients undergoing metastasectomy. - Conclusions - In selected patients who satisfied our surgical criteria, shrinkage rate of primary tumor and postchemotherapy serum CA19-9 level, which predict resectability of metastasized pancreatic cancer, should be considered in decision making to avoid unnecessary surgery.
Gesehen am 21.10.2019